Features of securing and guaranteeing the right to health care in the constitutions of the states of the world - Anishchenko, M. A.; Hamburh, I. A.; Maksakova, R.; Filei, Yu. V.; Аніщенко, Михайло Анатолійович (My University, 2021)
The article examines the features of securing and guaranteeing the right to health protection in the constitutions of the states of the world. The basis for the proclamation of the right to health by states at the constitutional level was the provisions of the basic international documents on human rights the Universal Declaration of Human Rights of 1948, the International Covenant on Economic, Social and Cultural Rights of 1966, the Convention for the Protection of Human Rights and Fundamental Freedoms (abbreviated – the European Convention on Human Rights) 1950 Those countries that ratified these documents, pledged to bring their legislation to the international standards enshrined in them. Therefore, the right to life, the right to health care are proclaimed in the constitutions of states as inalienable and inviolable. In many countries, the constitutional norm reflects not only the fact of the proclamation of the right, but contains provisions on its content, the means of guaranteeing the state the implementation of this right. These guarantees are state financing of health care sectors, different models of health insurance, reforming the medical system in matters of health care management, changes in the organizational and legal forms of health care institutions, the introduction of advanced principles, for example, “money follows the patient”, etc. The conclusion is made about the obligatory proclamation of the right to health care in the constitutions of all states of the world, the disclosure by the constitutional norms of the content and means of guaranteeing this right by the state.
Keywords: health protection; human rights; constitution; guarantees; legislation